MEDICINE TOURISM AND THEIR BENEFICIAL PROPERTIES IN THE MOUNTAIN CLUSTERS OF CHARVAK FREE TOURIST ZONE - Shomurodova Shahnoza Gayratovna (Ecomind Press, 2025)
Tourism opportunities develop based on the natural geographical location of each region. In particular, the development of medicinal tourism today is shaped by the beneficial properties of medicinal plants. This article describes in detail the development of medicinal tourism in the mountain clusters of the Charvak free tourist zone, as well as the healing properties of some medicinal plants that have been widespread in the nature of the zone since ancient times in the lower and upper adir regions, mountains and pastures, river and stream slopes, and on sandy and rocky terrain.
Keywords: Medicinal plants, environment, climate, humidity, flora, tourist zone.